Komodifikasi Tradisi Omed-Omedan Banjar Kaja Desa Adat Sesetan Kota Denpasar - Saskita, I Nyoman Urip Satyaraga Arya; Arjawa, I Gst. Pt. Bagus Suka; Kamajaya, Gede (Socio-political Communication and Policy Review, 2024)
This study aims to provide a comprehensive overview of the commodification process based on community initiatives, accompanied by complete information regarding the timeline and involvement of the actors. The form of commodification in this tradition is packaged in the form of a festival and the addition of cultural attractions and "peken paiketan" as attractions and added value in the festival's implementation. The process of commodification of the Omed-omedan tradition takes place in three stages: planning, preparation, and execution. The planning stage is related to the role of youth as initiators of the commodification of Omed-omedan into a festival form; they are also actively communicating the idea to traditional figures to obtain approval and support. The preparation stage involves facilitators, actors responsible for supporting festival activities from organizing work assignments, resource management to stakeholder negotiation. The facilitators involved include the traditional elders of Banjar Kaja Sesetan, the village chief of Sesetan Traditional Village, the Denpasar City Government, and sponsors. The execution stage involves all actors, especially the Banjar Kaja Sesetan community, STT, village security personnel, city government, media partners, and sponsors. Abstrak Penelitian ini diharapkan dapat memberikan gambaran utuh terkait proses komodifikasi tradisi yang berlangsung atas dasar inisasi masyarakat disertai dengan informasi lengkap terkait linimasa dan keterlibatan para aktor. Bentuk komodifikasi dalam tradisi ini yakni dikemas dalam bentuk festival serta penambahan atraksi budaya dan peken paiketan sebagai daya tarik dan nilai tambah dalam pelaksanaan festival. Proses komodifikasi tradisi Omed-omedan berlangsung dalam tiga tahapan yakni tahap perencanaan, persiapan dan eksekusi. Tahap perencanaan berkaitan dengan peran pemuda sebagai inisiator komodifikasi Omed-omedan menjadi festival, mereka juga aktif mengkomunikasikan ide tersebut kepada tokoh adat untuk mendapat persetujuan dan dukungan. Tahap persiapan berkaitan dengan fasilitator yakni aktor-aktor yang bertugas untuk mendukung kegiatan festival mulai dari penyusunan pembagian kerja, pengelolaan sumber daya hingga negosiasi stakeholder. Adapun fasilitator yang terlibat yakni prajuru adat Banjar Kaja Sesetan, Bendesa Desa Adat Sesetan, Pemerintah Kota Denpasar dan pihak sponsor. Tahap eksekusi melibatkan seluruh aktor khususnya masyarakat Banjar Kaja Sesetan, STT, pihak keamanan dari desa maupun pemerintah kota, media partner dan sponsor. Kata Kunci: Komodifikasi tradisi, Tradisi Omed-omedan, globalisasi.